Evaluasi Ketepatan Terapi Pada Pasien Diabetes Mellitus Tipe 2 Di Instalasi Rawat Inap Rsup Dr. Soeradji Tirtonegoro Klaten Periode Januari - Juni 2015 - Sepmawati, Nurul Dini; , Nurul Mutmainah, M.Si, Apt (2016)
The prevalence of metabolic disease, diabetes mellitus (DM) type 2, has increased every year. Since the beginning of this century, Indonesia is in the fourth position among other countries in the world with the highest population of DM. The purpose of this research was to find out the representation of therapy and accurateness drug treatment of DM type 2 in the inpatient installation of Dr. Soeradji Tirtonegoro Hospital, Klaten from January to June, 2015. This study is non-experimental research that analyzed by non-analytical descriptive method, the data was taken retrospectively, and the analysis was done based on the Guideline of Consensus Control and Diabetes Mellitus Type 2 Prevention in Indonesia (PERKENI, 2011), and American Diabetes Association guideline (2015). Based on the results of the research, from 72 patients it is concluded that the commonest antidiabetic drug given to the patient with DM type 2 is insulin 80.5%, metformin 22.2%, gliclazide 6.9%, glimepiride 5.6%, acarbose 2.8% and gliquidone 1.4%. The accurateness of therapy evaluation shows that 100% indication appropriate, 95.8% patient appropriate, 95.8% drug appropriate, and 100% dosage appropriate.